The correlation between visual display terminal utilization and the quality of life of bachelor of medicine students at Udayana University. - TJANDRA, DAVID CHRISTOPHER; ADNYANA, I. MADE OKA; UTAMI, DESAK KETUT INDRASARI; WIDYADHARMA, I. PUTU EKA (Family Medicine & Primary Care Review, 2025)
Background. Visual Display Terminal (VDT) is an electronic device that integrates and accesses various needs. The increasing use of VDT among students correlates with their quality of life. Objectives. This study aims to show the correlation between VDT utilization and students’ quality of life. Material and methods. This cross-sectional inferential analysis study focuses on the 2021 batch of medical students at Udayana University. Data was collected through a questionnaire and analyzed using SPSS version 26.0, employing Spearman’s correlation test. Results. Among 209 respondents, 85.20% used VDT ≤ 50 cm, 91.90% used VDT ≥ 4 hours, and 72.20% used > 2 VDT units. Most used VDT for entertainment (91%) purposes. While most students report a good quality of life, 0.48% had very poor physical health, and 0.96% had very poor psychological health. A positive correlation was found between device count (r = 0.178) and physical health, duration (r = 0.029) and device count (r = 0.114) with psychological health, viewing distance (r = 0.030) and device count (r = 0.189) with social relationships, and device count (r = 0.164) with environmental condition. Negative correlations were observed for viewing distance (r = -0.014) and duration (r = -0.031) with physical health, viewing distance (r = -0.013) with psychological health, duration (r = -0.043) with social relationships, and viewing distance (r = -0.195) and duration (r = -0.025) with environmental condition. Conclusions. Education on managing VDT usage is necessary to prevent declining quality of life. Students with moderate, poor, and very poor quality of life should receive immediate cognitive-behavioral therapy interventions. This study’s limitations include weak correlations between variables, a limited sample size, and the use of a self-report questionnaire.